Optimization of light transmission efficiency for nano-grating assisted MSM-PDs by varying physical parameters - Masouleh, F.; Das, Narottam; Mashayekhi, H. (Elsevier BV, 2014)
Metal–semiconductor–metal photodetectors (MSM-PDs) are utilized for suitable nano-structured fabrications that can play an important role for the development of future high-speed devices to achieve very high responsivity–bandwidth characteristics. Finite-difference time-domain (FDTD) method is used to calculate the light absorption enhancement factor of nano-grating assisted MSM-PDs near the design wavelength by changing the detector's geometrical parameters in comparison with a conventional device (i.e., without the nano-gratings). The substrates containing the aperture and the nano-gratings are optimized in thickness to trigger an extraordinary optical transmission. Besides, this paper demonstrates how the coupling condition satisfies the oscillating charge densities evolution to the surface plasmon polaritons under illumination of a polarized light and the existence of a band gap in the dispersion curve of surface plasmons propagating on periodically corrugated surfaces. The simulated results confirm that the light absorption enhancement factor of nano-grating assisted MSM-PDs is ~12-times better than the conventional type of MSM-PDs.